Prevalence and genotypes’ distribution of human papillomavirus among women in Saudi Arabia: a systematic review and meta-analysis - Aldossary, Mohammed S.; Mufrrih, Mohammed; El Dalatony, Mervat M.; Alamri, Hatoon M. (Frontiers in Public Health, 2025)
IntroductionHuman Papillomavirus (HPV) is a prevalent sexually transmitted infection that can lead to benign lesions, premalignant changes, and cancer. Despite its significance, studies in Saudi Arabia report inconsistent findings regarding HPV prevalence and risk factors. This systematic review and meta-analysis aimed to assess the prevalence and genotype distribution of HPV among women in Saudi Arabia.MethodsA systematic literature search was conducted across multiple electronic databases (January 1990–August 2024). Studies reporting HPV prevalence among women in Saudi Arabia, regardless of nationality or health status, were included. The pooled prevalence was calculated using a random-effects model, with log-transformed proportions and 95% confidence intervals (CI).ResultsTwenty-two studies (n = 15,224 women) met the inclusion criteria. The pooled prevalence of HPV among women attending cervical screening was 14.9% (95% CI: 10.9–18.9%), with substantial heterogeneity (I2 = 97.4%, p < 0.001). Subgroup analysis by region showed a higher prevalence in Riyadh (19.1, 95% CI: 13.1–25%) compared to the Western region (6.1, 95% CI: 3.7–8.4%). Among women with gynecological malignancies, the pooled prevalence was 68.1% (95% CI: 49–87.1%). HPV-16 was the most common genotype (35.4%), followed by HPV-18 (10.9%). Other high-risk types (HPV-45, 31, 33, 35, 52, and 58) accounted for 2.2–13.7% of infections.ConclusionHPV prevalence in Saudi Arabia is comparable to global figures, though significant geographic variability exists. A national screening survey is necessary to establish the true prevalence and inform preventive strategies.Systematic Review RegistrationPROSPERO No. CRD42024583260.